Bahaya Verbal Abuse terhadap Perkembangan Mental dan Kepercayaan Diri Anak - Indah Juliana (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Verbal abuse is a form of social violence that frequently occurs at home and in schools. This type of abuse includes mocking, insults, or degrading words often directed at children. This study aims to understand how verbal abuse impacts children’s mental development and self-confidence. By reviewing various related studies, the findings show that children who frequently experience verbal abuse tend to face mental health issues, such as low self-esteem, anxiety, and even depression. Additionally, they often lack self-confidence, which can affect their ability to interact with others and cope with life’s challenges. In conclusion, verbal abuse has a serious impact on children’s mental development and self-confidence, highlighting the need for preventive measures and support from family and community to create a safe environment that positively supports children’s growth and well-being.